Đàm thoại tiếng Anh hàng ngày. Tập 1 - Carney, Toney (Tổng hợp TP.HCM, 2011)
Job Application Form The Job Interview Mark's first day Responsibilities Job Description First Business Meeting First Contact With a Customer Meeting a Customer Presenting a Product to the Customer Negotiating a Deal Making a General Business Report